Sebuah PENILAIAN FRAMINGHAM RISK SCORE (FRS) UNTUK MEMPREDIKSI RISIKO PENYAKIT JANTUNG KORONER PADA PASIEN DIABETES MELLITUS TIPE II - Andi Fidianto; Andi Subandi; Putri Irwanti Sari; Yosi Oktarina; Riska Amalya Nasution (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
Coronary Heart Disease (CHD) is a leading cause of morbidity and mortality worldwide, including in Indonesia. Type II Diabetes Mellitus is an important risk factor because it increases the likelihood of cardiovascular events by 2–4 times through mechanisms such as chronic hyperglycemia, diabetic dyslipidemia, and endothelial dysfunction. Risk assessment using the Framingham Risk Score (FRS) is essential, as it can estimate the 10-year risk of CHD based on age, blood pressure, lipid profile, smoking status, and the presence of diabetes. The increase in DM cases at Raden Mattaher Hospital Jambi from 92 in 2023 to 125 in 2024 highlights the need for early cardiovascular risk detection. This study aimed to describe CHD risk in Type II DM patients using the FRS through a descriptive quantitative design involving 62 respondents. The results showed that 46 respondents (74.2%) were in the low-risk category, emphasizing that the FRS is useful in supporting clinical decision-making and planning preventive interventions for diabetic patients.